2023
DOI: 10.1002/ss.20467
|View full text |Cite
|
Sign up to set email alerts
|

Shining the light: Black women thriving in graduate school

Tamara Bertrand Jones,
Brittany Brewster,
Dawn Y. Matthews

Abstract: In this article, authors examine literature on the enrollment, degree attainment, and experiences of Black women graduate students. Authors use socialization to examine the failures of academia to account for Black women's intersectional identities and identify ways administrators and faculty can further support these women's success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…One of the documented ways Black women doctoral students have expressed potentially thriving at PWIs is through external mentorship (Jones et al, 2023). When recounting the past 20 years of academic literature related to Black graduate women’s experiences, Jones et al (2023) identified the significant role of external mentorship to unpack academia’s hidden curriculum. However, an overall systemic issue of lack in Black women faculty representation still leads Black graduate women to retain each other through peer mentoring and supports created by Black graduate women themselves (Jones et al, 2023).…”
Section: Black Women Doctoral Students’ Experiences At Pwismentioning
confidence: 99%
See 4 more Smart Citations
“…One of the documented ways Black women doctoral students have expressed potentially thriving at PWIs is through external mentorship (Jones et al, 2023). When recounting the past 20 years of academic literature related to Black graduate women’s experiences, Jones et al (2023) identified the significant role of external mentorship to unpack academia’s hidden curriculum. However, an overall systemic issue of lack in Black women faculty representation still leads Black graduate women to retain each other through peer mentoring and supports created by Black graduate women themselves (Jones et al, 2023).…”
Section: Black Women Doctoral Students’ Experiences At Pwismentioning
confidence: 99%
“…When recounting the past 20 years of academic literature related to Black graduate women’s experiences, Jones et al (2023) identified the significant role of external mentorship to unpack academia’s hidden curriculum. However, an overall systemic issue of lack in Black women faculty representation still leads Black graduate women to retain each other through peer mentoring and supports created by Black graduate women themselves (Jones et al, 2023). Though research has shown mentorship and faculty support to be critical to the success of Black women doctoral students (Patton, 2009; Patton & Harper, 2003), they still must create networks beyond their program, as they are rarely offered these supports within their doctoral programs, and in many cases, their institutions.…”
Section: Black Women Doctoral Students’ Experiences At Pwismentioning
confidence: 99%
See 3 more Smart Citations